2017
DOI: 10.1021/acs.inorgchem.7b01714
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extended Conjugation of N-Heterocyclic Carbene-Based Sensitizers on the Performance of Dye-Sensitized Solar Cells

Abstract: We report the synthesis, characterization, and photovoltaic properties of four ruthenium complexes (CI101, CBTR, CB111, and CB108) having various N-heterocyclic carbene ancillary ligands, pyridine-imidazole, -benzimidazole, -dithienobenzimidazole, and -phenanthroimidazole, respectively. These complexes were designed to investigate the effect of extended conjugation ordained from ring fusion on the power conversion efficiencies of the solar cells. The device sensitized by CB108, the pyridine-phenanthroimidazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Ruthenium­(II) polypyridyl compounds have been widely employed for several applications, notably in energy conversion processes, e.g., in artificial photosynthetic systems, , light-emitting devices, or solar cells. , Changes in the size and electronic features of the ligands are carried out to tune the properties of the complexes, such as light absorption, redox potential, reactivity, and energy level alignment, aiming to improve the efficiency of such devices . For the efficient preparation of these compounds, it is necessary to develop and understand the synthetic methods that allow the synthesis of coordination compounds that exhibit the properties required for a particular application in an easy and versatile way.…”
Section: Resultsmentioning
confidence: 99%
“…Ruthenium­(II) polypyridyl compounds have been widely employed for several applications, notably in energy conversion processes, e.g., in artificial photosynthetic systems, , light-emitting devices, or solar cells. , Changes in the size and electronic features of the ligands are carried out to tune the properties of the complexes, such as light absorption, redox potential, reactivity, and energy level alignment, aiming to improve the efficiency of such devices . For the efficient preparation of these compounds, it is necessary to develop and understand the synthetic methods that allow the synthesis of coordination compounds that exhibit the properties required for a particular application in an easy and versatile way.…”
Section: Resultsmentioning
confidence: 99%
“…The first type ( Figure 1 a) is N^C^N ligands containing two benzimidazole fragments, such as 2,6-bis(benzimidazol-2-yl)benzene [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The second type is C^N ligands ( Figure 1 b), where the Ru-C bond is formed with the imidazole fragment and one of the imidazole nitrogen is bonded to a pyridine [ 27 , 38 ]. The third type is the N^N ligands of the 2-benzimidazol-2-yl-pyridines class ( Figure 1 c) [ 27 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Complexes with ligands of the second type ( Figure 1 b) have also been studied as sensitizers for DSSC [ 38 ]. For example, the authors of [ 38 ] studied the effect of the size of the conjugated system of C^N-ligand on the photosensitizer efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In an independent study, Zhang and co-workers reported the synthesis of phenanthro-imidazole 1 (Figure 1) and used it for OLEDs [24]. More recently, Akula and coworkers have reported the synthesis of ruthenium complex 2, revealing good optical, electrochemical, and thermal properties, which has been used as a promising electron-transport material for organic solar cells [25].…”
Section: Introductionmentioning
confidence: 99%